Housing construction in the republic of Bashkortostan - E. Mamleeva; N. Trofimova; S. Marina (Вестник Северо-Кавказского федерального университета, 2022)
The purpose of the study is to analyze trends in the housing construction market in the Republic of Bashkortostan. In the course of the study, including using a systematic approach, as well as logical and statistical analysis, the features of the development of the housing construction market in the region in dynamics and in comparison with other subjects of the Volga Federal District were revealed. Despite the positive trends, problems were identified in the functioning of the housing construction market in the Republic of Bashkortostan, which persisted throughout the entire period of the study – 2010–2020: the presence of long-term construction and «deceived equity holders». Also, the issues of construction of engineering communications, infrastructure facilities, transport interchanges, regulation of building density in densely populated areas, etc. Have not been fully resolved; lack of professional staff, etc. One of the effective tools to stimulate housing construction in the region is the development of the housing mortgage lending market. The authors present an overview of the mortgage lending market in the region. In conclusion, the problems of the functioning of the housing construction market in the Republic of Bashkortostan are outlined.